Vasyl Yermilov legacy in the cultural context of independent Ukraine - Колісник, О. В.; Подобєд, К. І. (Art and Design, 2021)
To examine Ukrainian art projects and studies of the period of independence, dedicated to the legacy of the outstanding artist and designer Vasyl Yermilov, and to actualize the significance of the artist's work for the contemporary art and design process. Methods of systematization and actualization of the analytical information gained by studying specialized professional literature and websites of cultural institutions. The main tendencies of work with the legacy of Vasyl Yermilov in the context of the problems of the Ukrainian avant-garde are determined and characterized. The issue of the importance of differentiating the Ukrainian and Russian avant-garde on the international art scene for the formation of a positive image of Ukraine has been actualized. Key projects were analyzed, including museum and contemporary art exhibitions, and the difficulty of working with the artist’s legacy due to the lack of iconic works in Ukrainian collections and the loss of some of the works of the 1920s was raised. Systematized Ukrainian art projects and studies of the period of independence, dedicated to Vasyl Yermilov, which cover various areas of culture: art history works, museum exhibition projects, contemporary art practices. The study shows current trends in working with the heritage of the Ukrainian avant-garde and can be used to develop further cultural projects and create exhibitions.